Heroes from the past : their beliefs and practices, and influence on current science education practice. - White, Robyn C. (Curtin University, 1998)
This study reflects my own search to clarify the process of cultural change in an educational setting. In particular it clarifies for me the process through which State-wide science curriculum reform was enacted in the late 1950s and into the 1970s. This period is interesting because of a continuing perception amongst science teachers that the system-wide changes of the time were widely supported by teachers and influenced classroom practice. My aim in this study was to explore how the characteristics of this cultural change process may be applied in the current climate of school reform.The members of the local science teacher community of the 1950s, 1960s and 1970s engaged in similar activities and conversations as they attended the same University then continued to enter into similar school-based activities. As a group of people with shared experiences and values, who made decisions based on similar understandings and priorities, this group may be regarded as an identifiable culture.The day to day activities of this community of science teachers were underpinned by each teacher's beliefs about scientific knowledge and processes and school science, as well as understandings about the teaching and learning process. Many of these beliefs were so fundamental as to be unquestioned, and may be referred to as referents, or myths. For the members of a culture to change their practice then, new referents must be introduced, or existing referents modified.In searching for the process by which this culture was able to access new understandings, this study examined the comparative influence of two highly visible science educators who promoted science curriculum change in the State. As a result of data collection involving interviews with twenty-five key informants and the examination of private and public archival records; the crucial role of these unique personalities emerged consistently: Each of these men have been characterised as a Hero because each brought new understandings to their existing culture (Campbell, 1949).In reviewing the extended career of each Hero it was possible to draw strong parallels with mythical Greek heroes, Perseus and Theseus. This metaphorical representation not only effectively mirrored the life history of the modern-day heroes but also served to reconnect the logic of science along with that of the emotion of art - a balance well understood by the Greeks.The study found that the successful Heroes promoted significant long term change by instituting new rituals, ceremonies and artefacts throughout the science education community. Over time, these activities effectively modified older referents and created new ones, leading to new practice in the curriculum enacted by science teachers.In drawing together the stories of Perseus and Theseus, it was possible to recognise common elements in the processes by which these influential individuals were able to effect new practice in their community. Thus the study provides a template for the cultural change process in the future.In the final discussion, focus shifts to the relevance of this research to the everyday enterprise of schools and school systems. As a school practitioner z always read scholarly papers with the underpinning question; "See What?" The final chapter then, is largely hypothetical as it poses possibilities, makes predications and offers advice for readers seeking to improve the change process in their own context.